Pancreatic cancer spheres are more than just aggregates of stem marker-positive cells. Issue 1 (4th October 2010) - Gaviraghi, Margherita; Tunici, Patrizia; Valensin, Silvia; Rossi, Marco; Giordano, Cinzia; Magnoni, Letizia; Dandrea, Mario; Montagna, Licia; Ritelli, Rossana; Scarpa, Aldo; Bakker, Annette
Abstract : Pancreatic cancer stem-like cells are described by membrane expression of CD24, CD44 and ESA (epithelial-specific antigen) and their capacity to grow as spheres in a serum-free medium containing well-defined growth factors. The capacity of a panel of four pancreatic cancer cell lines (PANC-1, CFPAC-1, PancTu-1 and PSN-1) to form spheres was tested. All cell lines with the exception of PancTu-1 developed spheres. Phenotypically, the sphere-growing cells showed an increased in vitro invasion capability. Both gene and protein expressions of markers of metastases [CXCR4 (CXC chemokine receptor 4), OPN (osteopontin) and CD44v6] and components of active hedgehog pathway signalling were assessed. Spheres clearly demonstrated increased expression of the above-mentioned markers when compared with their adherent counterpart. With the aim of identifying a minimum set of markers able to separate cells that have the capacity to form spheres from those incapable of forming spheres, a PCA (principal component analysis) of the multidimensional dataset was performed. Although PCA of the 'accepted' stemness genes was unable to separate sphere-forming from sphere-incapable cell lines, the addition of the 'aggressiveness' marker CD44v6 allowed a clear differentiation. Moreover, inoculation of the spheres and the adherent cells in vivo confirmed the superior aggressiveness (proliferation and metastasis) of the spheres over the adherent cells. In conclusion, the present study suggests that the sphere-growing cell population is not only composed of cells displaying classical stem membrane markers but also needs CD44v6-positive cells to successfully form spheres. Our results also emphasize the potential therapeutic importance of pathways such as CXCR4 and hedgehog for pancreatic cancer treatment.